Pathology, organ distribution, and immune response after single and repeated intravenous injection of rats with clinical-grade parvovirus H1 - Geletneky, Karsten; Hajda, Jacek; Rommelaere, Jean (Comparative medicine, 2015)
Parvovirus H1 (H1PV) is an autonomous parvovirus that is transmitted in rodent populations. Its natural host is rats. H1PV infection is nonpathogenic except in rat and hamster fetuses and newborns. H1PV infection of human cancer cells caused strong oncolytic effects in preclinical models. For a clinical trial of H1PV in patients with brain tumors, clinical-grade H1PV was produced according to Good Manufacturing Practices. This report focuses on results obtained after a single high-dose intravenous injection of highly purified H1PV in 30 rats and multiple (n = 17) intravenous injections at 3 dose levels in 223 rats. In both studies, no virus-related mortality or macroscopic organ changes related to H1PV occurred. Histopathology after multiple virus injections revealed minimal diffuse bile duct hyperplasia in livers of animals of the highest dose group and germinal center development in spleens of animals from the high-dose group. Liver changes were reversible within a 2-wk recovery period after the last injection. Hematology, blood chemistry, and coagulation analyses did not reveal significant toxicologic changes due to H1PV. Virus injection stimulated the production of IgG antibodies but did not alter mononuclear cell function or induce cytokine release. PCR analysis showed dose-dependent levels of viral genomes in all organs tested. The virus was excreted primarily through feces. These data provide important information regarding H1PV infection in its natural host. Due to the confirmation of the favorable safety profile of H1PV in a permissive animal model, a phase I/IIa clinical trial of H1PV in brain tumor patients could be initiated.